Preliminary Report on the Effect of Pre-Boring on the Mobilized Friction Capacity of Pile Foundation Hydraulically Jacked into Expansive Soil - Gogot Setyo Budi (Institute of Research and Community Outreach - Petra Christian University, 2015)
Pre-drilling was performed to reduce lateral earth pressure generated by pile foundation hydraulically jacked into expansive soil. Nineteen prestressed-precast spun concrete pile with diameter of 800 mm were penetrated into expansive soil up the depth of 40 m. Pre-drilling with diameter of 700 mm was carried out up to the depth of 12.5 m. Penetration loads required to install the piles, which was displayed on the built-in pressure panel, were recorded every 1 m interval. The load that was consisted of merely shaft friction was then used to find out the mobilized skin friction between pile shaft and its surrounding soils. The calculated mobilized skin friction was correlated to the value of Standard Penetration Test (NSPT) and compared to Decourt formula. The result shows that skin friction calculated using Decourt formula relatively conservative compared to those determined from the records of field penetration. The upper bound of mobilized skin friction can be defined by modifying Decourt formula.